2020
DOI: 10.5194/gmd-2020-249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Coupling a Stochastic Convective Parameterization with Zhang-McFarlane Scheme on Precipitation Simulation in the DOE E3SMv1 Atmosphere Model

Abstract: Abstract. A stochastic deep convection parameterization is implemented into the U.S. Department of Energy (DOE) Energy Exascale Earth System Model (E3SM) Atmosphere Model version 1 (EAMv1). This study evaluates its performance on the precipitation simulation. Compared to the default model, the probability distribution function (PDF) of rainfall intensity in the new simulation is greatly improved. Especially, the well-known problem of too much light rain and too little heavy rain is alleviated over the tropics.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…A detailed description of the implementation of the stochastic scheme and its overall performance in the climate models can be found in Y. Wang et al. (2016, 2021). Two AMIP‐type simulations are conducted using the observed monthly sea surface temperatures and sea ice extent as lower boundary conditions, with the standard ZM scheme (CAM5) and the addition of the stochastic scheme (STOC), respectively.…”
Section: Model Experiments and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the implementation of the stochastic scheme and its overall performance in the climate models can be found in Y. Wang et al. (2016, 2021). Two AMIP‐type simulations are conducted using the observed monthly sea surface temperatures and sea ice extent as lower boundary conditions, with the standard ZM scheme (CAM5) and the addition of the stochastic scheme (STOC), respectively.…”
Section: Model Experiments and Datamentioning
confidence: 99%
“…Recently, Y. Wang et al. (2016, 2021) successfully suppressed the excessive occurrence of light rain by incorporating a stochastic convective scheme (Plant & Craig, 2008) into the Zhang‐McFarlane deep convection scheme (Zhang & McFarlane, 1995) in two GCMs. The improved rainfall frequency simulation provides a unique opportunity to address the above questions.…”
Section: Introductionmentioning
confidence: 99%
“…Wang, Xia, et al. (2021) showed that, when light rain was suppressed by improving convection parameterization (Y. Wang, Zhang, et al., 2021; Y. Wang et al., 2016, 2017), it had a profound impact on the atmospheric aerosol concentration. The aerosol optical depth (AOD) increased at the global scale, especially in the rain belts over the tropics and subtropics, by as much as 0.3.…”
Section: Introductionmentioning
confidence: 99%